PLL-less three-phase four-wire SAPF with STF-ԁԛ0 technique for harmonics mitigation under distorted supply voltage and unbalanced load conditions - Hoon, Yap; Mohd Radzi, Mohd Amran (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
This paper presents a non-iterative technique that generates reference current to manage operation of a three-phase four-wire shunt active power filter which employs a three-leg split capacitor voltage source inverter (VSI) topology. The proposed technique integrates together a self-tuning-filter (STF) and direct-quadrature-zero (dq0) principle (referred here as STF-dq0), allowing the controlled shunt active power filter (SAPF) to perform effectively under distorted source voltages and unbalanced load conditions. Unlike the previous technique developed based on the standard dq0 principle, the proposed technique does not require any service from a phase-locked loop (PLL) where two STFs are applied to separate harmonic and fundamental elements for the purpose of generating synchronization phases and reference current, respectively. Simulation work which includes connection of the SAPF circuits, design of control techniques and all the necessary assessments are conducted in MATLAB-Simulink platform. Performance achieved by the SAPF while utilizing the proposed technique is thoroughly investigated and benchmarked with that demonstrated by the SAPF while using the standard dq0 technique, to evaluate the inherent advantages. Exhaustive simulation results are provided and thoroughly discussed to support design concept, effectiveness, and benefits of the proposed technique.